2021
DOI: 10.3390/polym13101600
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Effect of Ionic Liquid Pretreatment on the Eucalyptus Kraft Pulp during Oxygen Delignification Process

Abstract: Oxygen delignification presents high efficiency but causes damage to cellulose, therefore leading to an undesired loss in pulp strength. The effect of ionic liquid pretreatment of [BMIM][HSO4] and [TEA][HSO4] on oxygen delignification of the eucalyptus kraft pulp was investigated at 10% IL loading and 10% pulp consistency, after which composition analysis, pulp and fiber characterizations, and the mechanism of lignin degradation were carried out. A possible dual effect of enhancing delignification and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Moreover, the authors reported an unusual reduction of pulp brightness, which is due to the formation of Hibbert’s ketones and quinonoids as the β-O-4 bonds cleave during oxygen delignification. Dissolved lignin fragments migrated onto the fibers’ surface thereby protecting their framework from oxidative damage …”
Section: Chemical and Physicochemical Delignification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the authors reported an unusual reduction of pulp brightness, which is due to the formation of Hibbert’s ketones and quinonoids as the β-O-4 bonds cleave during oxygen delignification. Dissolved lignin fragments migrated onto the fibers’ surface thereby protecting their framework from oxidative damage …”
Section: Chemical and Physicochemical Delignification Methodsmentioning
confidence: 99%
“…Moreover, the authors reported an unusual reduction of pulp brightness, which is due to the formation of Hibbert's ketones and quinonoids as the β-O-4 bonds cleave during oxygen delignification. Dissolved lignin fragments migrated onto the fibers' surface thereby protecting their framework from oxidative damage 241. Achinivu et aldeveloped protic ionic liquids (PILs) by reacting acetic acid with pyridine ([Py][Ac]), 1-methylimidazole ([Mim][Ac]) or pyrrolidine ([Pyrr][Ac]).…”
mentioning
confidence: 99%